Misfit dislocation in a precipitate/matrix interface of any orientation relative to the matrix free-surface - Colin, J. (Archives of Mechanics, 2020)
The presence of an edge dislocation in a surface of a two-dimensional precipitate of square shape embedded in a semi-infinite matrix has been discussed when the precipitate is submitted to misfit strain due to the lattice mismatch between the two phases. Considering any orientation of the precipitate relative to the matrix free-surface, the total force applying on the dislocation has been analytically calculated and its equilibrium position has been determined. The conjugated effects of the precipitate misorientation, of the lattice mismatch and of the precipitate/matrix distance have been finally characterized. A shifting effect on this equilibrium position has been analyzed.